A Comparative Cross‑Cultural Analysis of the Profile of A Modern Ukrainian Manager: the Imperatives of the Future in the Context of Internationalization - Beata Glinkowska; Viacheslav A. Chebotarov (Comparative Economic Research. Central and Eastern Europe, 2018)
The preliminary results of the development of the initial theoretical, methodological and applied methodological provisions for the study of the profile of a modern Ukrainian manager are presented in the context of predicting its transformation in the future in the context of deepening internationalization. The results of the Polish-Ukrainian applied empirical analysis carried out by the authors are discussed. The content of the parameters of a modern Ukrainian manager is disclosed in the framework of the most common models of national business cultures, and directions for the further scientific, practical and methodological development of the problem are determined.
Keywords: D90; 330; internationalization; manager profile; cross-culture; national business culture; Poland; Ukraine; parameters; competences; comparative analysis